Compliance of corporate businesses to health and environment standards. The case of cell phone towers in Egypt - Ibrahim, Mohamed Mostafa (AUC Knowledge Fountain, 2015)
This study explores the compliance of corporate businesses to the health and environment standards especially, the construction of cell phone towers, in Egypt. Also, it examines to what extent the mobile companies in Egypt adhere to the health and environment standards, namely in the residential areas (informal and poor areas). It demonstrates how the standards set in Egypt are not applied restrictively enough to ban the violations. Besides, there are negative impacts that might be found as a result of not complying with the health standards. In this study, the qualitative research methods were used in the form of in-depth interviews with the three mobile companies (Vodophone, Mobinil, Etisalat) and the Egypt governmental body (NTRA). The research findings showed that mobile companies in Egypt do not comply with the health and environment standards in many cases. In terms of health and environment standards, the study, based on the interviews in addition to the literature review, showed that setting up cell phone tower stations on the buildings' roofs has negative impact in case of not complying with standards. Therefore, it could be considered as a source of danger, especially, to those who live close to towers. Also, the NTRA’s standards are not strong enough to ban the violations compared to other countries (Turkey, Tunisia, and South Africa). Moreover, the study reveals some reasons behind the violations such as: delivering good coverage, people’s attitude, building violations, and the most important reason is the weak role of the governmental body represented by the NTRA